2010
DOI: 10.3844/ajassp.2010.56.62
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Thermophilic Cellulase-Producing Bacteria from Empty Fruit Bunches-Palm Oil Mill Effluent Compost

Abstract: Problems statement: Lack of information on locally isolated cellulase-producing bacterium in thermophilic compost using a mixture of Empty Fruit Bunch (EFB) and Palm Oil Mill Effluent (POME) as composting materials. Approach: The isolation of microbes from compost heap was conducted at day 7 of composting process where the mixture of composting materials consisted of 45.8% cellulose, 17.1% hemicellulose and 28.3% lignin content. The temperature, pH and moisture content of the composting pile at day 7 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 24 publications
(26 reference statements)
0
22
0
4
Order By: Relevance
“…Therefore, it is possible that the inoculation of the compost with B. cereus increased the decomposition of that polymer. Some studies have reported the high cellulolytic potential of particular species of bacteria isolated from composting, such as those belonging to the genus Bacillus (Baharuddin;Razak;Hock, 2010;Lynd et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that the inoculation of the compost with B. cereus increased the decomposition of that polymer. Some studies have reported the high cellulolytic potential of particular species of bacteria isolated from composting, such as those belonging to the genus Bacillus (Baharuddin;Razak;Hock, 2010;Lynd et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…On the 23rd day (T10) the peaks associated with Treatments 3 and 4 were quite obvious in the region belonging to the inocula. The species of bacteria utilized as inocula are thermophiles, being plentiful in that phase of the process and together with fungi are responsible for cellulose degradation (Baharuddin;Razak;Hock, 2010;Lynd et al, 2012).Bacterias do genero Bacillus apresentam alta capacidade metabólica de degradar substâncias recalcitrantes como lignina e celulose, however. During the process, environmental conditions are mostly responsible for microbial fluctuations, and composting microbiota depends on its own competitive effectiveness and its survival capacity.…”
Section: Molecular Analysis During Compostingmentioning
confidence: 99%
“…Bacteria which have high growth rate as compared to fungi have good potential to be used in cellulase production. For this application, the utilization of thermophilic cellulolytic microbes is more advantageous than the mesophilic one because the cellulase enzyme produced remains stable at high temperature and still has optimum activity [2]. Thermostable cellulase enzymes with high stability can be obtained by isolating from thermophilic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Amplification of the gene was carried out by PCR using Marchesi specific primer 63f (5'-CAG GCC TAA CAC ATG CAA GTC-3') and 1387r (5'-GGG CGG WGT GTA CAA GGC-3') (Wahyudi et al, 2010). The PCR condition was set up 30 cycles (Baharuddin et al, 2010) with pre-denaturing step at 94°C for 2 min, denaturing at 92°C for 30 sec, annealing at 55°C for 30 sec, polymerization at 75°C for 1 min and post PCR at 75°C for 5 min. The PCR products, approximately 1300 bp, were purified and sequenced using ABI 310 (Perkin Elmer, USA).…”
Section: Screening and Selection Of Chitinolytic Activitymentioning
confidence: 99%